Non‐Lithography Hydrodynamic Printing of Micro/Nanostructures on Curved Surfaces. Issue 34 (15th July 2020) - Su, Meng; Qin, Feifei; Zhang, Zeying; Chen, Bingda; Pan, Qi; Huang, Zhandong; Cai, Zheren; Zhao, Zhipeng; Hu, Xiaotian; Derome, Dominique; Carmeliet, Jan; Song, Yanlin
Abstract: A key issue of micro/nano devices is how to integrate micro/nanostructures with specified chemical components onto various curved surfaces. Hydrodynamic printing of micro/nanostructures on three‐dimensional curved surfaces is achieved with a strategy that combines template‐induced hydrodynamic printing and self‐assembly of nanoparticles (NPs). Non‐lithography flexible wall‐shaped templates are replicated with microscale features by dicing a trench‐shaped silicon wafer. Arising from the capillary pumped function between the template and curved substrates, NPs in the colloidal suspension self‐assemble into close‐packed micro/nanostructures without a gravity effect. Theoretical analysis with the lattice Boltzmann model reveals the fundamental principles of the hydrodynamic assembly process. Spiral linear structures achieved by two kinds of fluorescent NPs show non‐interfering photoluminescence properties, while the waveguide and photoluminescence are confirmed in 3D curved space. The printed multiconstituent micro/nanostructures with single‐NP resolution may serve as a general platform for optoelectronics beyond flat surfaces. Abstract : Curveball : A non‐lithography hydrodynamic printing strategy is proposed for preparing micro/nanostructures on three‐dimensional curved surfaces. A capillary pumped function between the template and curved substrates assembles nanoparticles on curved surfaces at the resolution of single nanoparticles. The strategy provides a general platform for optoelectronics beyond flat surfaces.